Apakah Tax Aggressive Indikator Manajemen Laba? dengan Ukuran Perusahaan sebagai Variabel Moderasi - Al Gifari, Muhammad Chaidir; Khomsiyah, Khomsiyah (Universitas Batanghari Jambi, 2024)
This research aims to obtain empirical evidence regarding the impact of independent variables, namely tax aggressiveness and leverage on earnings management as the dependent variable with company size as the moderating variable. The population used in this research is manufacturing companies listed on the Indonesia Stock Exchange (BEI) from 2019 to 2022. The results of this research reveal that there is no strong evidence regarding the influence of tax aggressiveness on earnings management actions. Leverage is proven to have a positive and significant influence on earnings management practices, and the company size variable is found to neither strengthen nor weaken the relationship between tax aggressiveness and earnings management practices. However, company size has the ability to weaken the relationship between leverage and earnings management practices.